2019
DOI: 10.1016/j.ejvs.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Sub-threshold Abdominal Aortic Aneurysms Undergoing Surveillance in Patients Aged 85 Years or Over

Abstract: Evidence on the surveillance of small abdominal aortic aneurysms (AAAs) in patients aged 85 years is limited. This study suggests that it might be safe to discontinue surveillance in patients aged 85 years with an AAA <40 mm, and that early assessment of surgical fitness in patients with larger aneurysms may reduce unnecessary investigations.Objective: Despite an increasing elderly population there is limited evidence regarding the surveillance and management of small abdominal aortic aneurysms (AAAs) in octog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…A total of 14 studies included 69,579 participants with unrepaired AAA with a mean follow-up time of 5.4 years ( Figure 1 ). Nine studies were prospective cohort studies [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and five studies were retrospective cohort studies [ 17 , 18 , 19 , 20 , 21 ]. Twelve studies reported the incidence of cardiovascular death in 35,936 participants [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 studies included 69,579 participants with unrepaired AAA with a mean follow-up time of 5.4 years ( Figure 1 ). Nine studies were prospective cohort studies [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and five studies were retrospective cohort studies [ 17 , 18 , 19 , 20 , 21 ]. Twelve studies reported the incidence of cardiovascular death in 35,936 participants [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were prospective cohort studies [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and five studies were retrospective cohort studies [ 17 , 18 , 19 , 20 , 21 ]. Twelve studies reported the incidence of cardiovascular death in 35,936 participants [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 ]. Five studies reported the incidence of non-fatal MI and non-fatal stroke in 35,860 participants [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary evidence suggests that not offering AAA surveillance to those aged > 85 years with an AAA diameter < 40 mm is a justified approach. 2 Certainly, based on the findings in this study, an earlier determination of fitness for surgery should be made to prevent unnecessary surveillance of patients who are unlikely ever to be candidates for intervention. Ideally, such a decision should be made after multidisciplinary team review and discussion with patient and family.…”
mentioning
confidence: 88%
“…A retrospective cohort study of elderly pts, aged ! 85 years, with AAA 3.0-5.4 cm in diameter at baseline, showed that discontinuation of follow-up might be safe in aneurysms measuring < 4 cm in diameter at baseline [316]. For elderly pts with aneurysms measuring 4-5.4 cm in diameter, assessment of fitness for surgery may prevent unnecessary surveillance [316].…”
Section: Follow-up Of Small Abdominal Aortic Aneurysmmentioning
confidence: 99%